2021
DOI: 10.1002/ecy.3519
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks

Abstract: Species assemblages often have a non-random nested organization, which in vertebrate scavenger (carrion-consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Although such obligate scavengers were absent from our study system, we found wild boar to be the dominant scavenger, with its presence enhancing the carcass decomposition speed (Figure 4a). Wild boar belonged to the species with the highest intraspecific interaction behavior (Table 2), indicating their social nature (e.g., Dardaillon, 1988; Maselli et al, 2014; Sebastián‐González et al, 2021). These results do not suggest that interspecific interactions between wild boar and other species did not occur, but is presumably a limitation of the annotation protocol that we used since we only annotated the longest and second‐longest shown behavioral type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such obligate scavengers were absent from our study system, we found wild boar to be the dominant scavenger, with its presence enhancing the carcass decomposition speed (Figure 4a). Wild boar belonged to the species with the highest intraspecific interaction behavior (Table 2), indicating their social nature (e.g., Dardaillon, 1988; Maselli et al, 2014; Sebastián‐González et al, 2021). These results do not suggest that interspecific interactions between wild boar and other species did not occur, but is presumably a limitation of the annotation protocol that we used since we only annotated the longest and second‐longest shown behavioral type.…”
Section: Discussionmentioning
confidence: 99%
“…Different scavenger species may fulfill different functional roles in the carcass decomposition process (Sebastián‐González et al, 2020, 2021), which would be reflected in differences in behavior and preferences for tissues types. For example, Young et al (2014) observed that common buzzards ( Buteo buteo ) fed primarily on soft tissues in the early stages of decomposition, while carrion crows ( Corvus corone ) increased their feeding as carcasses went into later stages of decomposition and exploited more different body parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are key differences that may drive divergent predator-prey dynamics and zoogeochemical effects in aquatic versus terrestrial environments (Strong 1992); for example, wet environments can promote bone decomposition (Subalusky et al 2017) whereas nutrients may remain locked in bones for longer periods in dry terrestrial ecosystems, and nutrients deposited into flowing water may be transported over much greater distances than terrestrial inputs. We see research that focuses on functional traits of animals (sensu Schmitz and Leroux 2020, McCary and Schmitz 2021, Sebastián-González et al 2021, Suraci et al 2021 combined with an understanding of key ecosystem characteristics as the way forward for disentangling these context dependencies to yield broader insights. As an example, identifying which predator-prey interactions are most likely to yield strong spatial responses in food webs with multiple predators and prey (Palmer and Packer 2021), how individual prey species responses to predators aggregate to determine net prey community effects on biogeochemistry (le Roux et al 2018(le Roux et al , 2020 and understanding underlying patterns of nutrient colimitation (Kaspari and Powers 2016), will allow for a stronger mechanistic understanding of the role animals play in spatial ecosystem configuration.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Obligate scavengers are excellent at detecting carrion, as a result, lead to carcasses being consumed faster 8 , 9 . Specifically, while obligate scavengers are highly efficient at consuming carrion, they also promote the interspecific interactions with other scavengers by signaling carcass locations while also opening large carcasses and allowing other scavengers access, thereby enhancing the carcass consumption rate 6 , 10 , 11 . But scavenging by facultative scavengers (species that opportunistically feed on carrion such as carnivora and raptors 12 ) is also widespread, even in the absence of vultures (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 ). Facultative scavengers also include some key species, with high olfactory acuity and social foragers, playing an important ecological role in the facilitation of carrion consumption in a scavenger community 11 . Thus, it is important to understand ecosystem function (i.e., carrion consumption) by the facultative scavenger community in a system where obligate scavengers are absent.…”
Section: Introductionmentioning
confidence: 99%